UBTF Mutation Causes Complex Phenotype of Neurodegeneration and Severe Epilepsy in Childhood - Sedláčková, Lucie; Laššuthová, Petra; Štěrbová, Katalin; Haberlová, Jana; Vyhnálková, Emílie; Neupauerová, Jana; Staněk, David; Šedivá, Marie; Kršek, Pavel; Seeman, Pavel (Neuropediatrics, 2019)
Introduction Neurodegenerative diseases of childhood present with progressive decline in cognitive, social, and motor function and are frequently associated with seizures in different stages of the disease. Here we report a patient with severe progressive neurodegeneration with drug-resistant epilepsy of unknown etiology from the age of 2 years.Methods and Results Using whole exome sequencing, we found heterozygous missense de novo variant c.628G > A (p.Glu210Lys) in the UBTF gene. This variant was recently described as de novo in 11 patients with similar neurodegeneration characterized by developmental decline initially confined to motor development followed by language regression, appearance of an extrapyramidal movement disorder, and leading to severe intellectual disability. In 3 of the 11 patients described so far, seizures were also present.Conclusions Our report expands the complex phenotype of neurodegeneration associated with the c.628G > A variant in the UBTF gene and helps to clarify the relation between this one single recurrent pathogenic variant described in this gene to date and its phenotype. The UBTF gene should be considered a novel candidate gene in neurodegeneration with or without epilepsy.
Keywords: UBTF; neurodegeneration; epilepsy; whole exome sequencing; trio analysis